A novel benzothiadiazole-based and NIR-emissive fluorescent sensor for detection of Hg2+ and its application in living cell and zebrafish imaging. Issue 32 (6th August 2020) - He, Haifeng; Meng, Xiangying; Deng, Lili; Sun, Qi; Huang, Xuelong; Lan, Ning; Zhao, Feng
Abstract : The probe TBBA exhibited excellent analytical properties with a remarkably large Stokes shift (195 nm), rapid response, high selectivity and sensitivity, good binding constant (2.37 × 10 4 M −1 ) and low LOD (13.10 nM). Abstract : The development of a novel near-infrared (NIR) probe for the detection of toxic Hg 2+ in organisms with high selectivity and sensitivity is of great interest but remains a great challenge. Hence, in this work, a new NIR fluorescence enhanced sensor (TBBA ), which contains a D–A structure as the NIR fluorophore and rhodanine-3-acetic acid as the receptor, has been developed for the detection of Hg 2+ with high selectivity, sensitivity, low limit of detection (13.10 nM) and good binding constant (2.37 × 10 4 M −1 ). The mechanism of TBBA response to Hg 2+ was further proved by 1 H NMR titration, HRMS, and theoretical calculations. Furthermore, TBBA is applied as a fluorescent probe for imaging living cells and zebrafish, indicating that it can be potentially applied for Hg 2+ sensing in both environmental and biology fields.